Dynamics of excited-state intramolecular proton-transfer in 2-amino-3-(2′-benzazolyl)quinoline cations. Issue 7 (5th June 2017) - Khimich, Mikhail N.; Ivanov, Vladimir L.; Melnikov, Mikhail Ya.; Shelaev, Ivan V.; Gostev, Fedor E.; Nadtochenko, Victor A.; Uzhinov, Boris M.
Abstract : Using femtosecond absorption spectroscopy and nanosecond fluorescence spectroscopy, the effective ESIPT time in the cations was determined, which increased with decreasing temperature. Abstract : It was found that cations formed by the protonation of 2-amino-3-(2′-benzoxazolyl)-quinoline (ABO) and 2-amino-3-(2′-benzothiazolyl)-quinoline (ABT) at the nitrogen atom of the quinoline ring exhibit excited-state intramolecular proton transfer (ESIPT). The two-band fluorescence of these cations is due to the emission from two species: the initial tautomer (short-wavelength band) and the ESIPT product (long-wavelength band). The relative intensity of the long-wavelength band depends on the basicity of the proton-accepting moiety and temperature. Quantum-chemical calculations demonstrated that ESIPT in cations involves overcoming a significant potential barrier, which increases with the decreasing basicity of the proton-accepting benzazole moiety. Using femtosecond absorption spectroscopy and nanosecond fluorescence spectroscopy, the effective ESIPT time in the studied cations was determined, which increased with decreasing temperature.